Sistem Informasi Evaluasi Nilai Berbasis Aturan di Kabupaten Soppeng - Riangdana Jurmasari; Farida Yusuf; Asrul Azhari Muin (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
The student assessment system at SDN 191 Penrie currently relies on grade books, which often leads to recording errors, delays in report preparation, and a lack of transparency between teachers and parents. This study aims to develop and evaluate the effectiveness of a grade evaluation information system in improving the daily assessment process. The research approach used a mixed method, combining qualitative methods through observation, interviews, and document analysis to identify existing system flows, as well as quantitative methods using a Likert scale questionnaire to measure the effectiveness of the system before implementation and testing the System Usability Scale (SUS) to assess the extent to which the system can assist teachers. The main findings using the Likert scale show that the effectiveness of the system before implementation reached a score of 56.19, while after implementation, the SUS score reached 93.2, indicating an increase in assessment effectiveness. In conclusion, this system is effective in supporting accurate and transparent daily assessments, thereby having a positive impact on improving the quality of basic education in line with the principles of honesty and fairness.